Odgovornost pravnih poklicev - teorija in praksa - Mežnar, Špela (Pravni letopis, 2008)
Within Slovenian legal system, bankruptcy administrators, executors, mediators, arbitrators, lawyers and public notaries perform different roles and functions. Aoccordingly, their civil liability is subject to different rules. The only common feature is that every profession is legally responsible for damage caused by the breach of due-diligence. While lawyers, public notaries and executors are liable according to general rules on civil liability, the liability of arbitrators is narrower. The reason lies in the very nature of the arbitration proceeding and arbitral award, which is legally identical to the effect of a civil law judgment (res judicata).
Keywords: odgovornost; odškodninska odgovornost; pravniki